Capture and release of CO2 by polyamidine. Issue 16 (16th May 2013) - Furusho, Yoshio; Endo, Takeshi
ABSTRACT: By CO2 bubbling into an aqueous dimethyl sulfoxide solution, the polyamidine (Poly‐Amd ) prepared from hexamethylenediamine and triethyl orthoacetate was converted to the bicarbonate salt, Poly‐Amd H·HCO3, which formed aggregates. Conversely, the aggregates disappeared upon Ar bubbling to release the captured CO2, reverting to Poly‐Amd completely. Polyethyleneimine (PEI ) also reversibly captured and released CO2 molecules in solution by bubbling CO2 and Ar, respectively, in an alternate manner. No appreciable difference was observed between Poly‐Amd and PEI in CO2 capture in solution. The binary system consisting of Poly‐Amd and polyethylene glycol (PEG ) captured CO2 efficiently at ordinary pressure and reached a stationary state within 200 h, at which 66% of the amidine groups bound CO2 molecules, which was released upon exposure to a N2 flow. In contrast to the binary system with Poly‐Amd, the binary system of PEI with PEG did not capture CO2 efficiently, and only 5.7% of the amino groups bound CO2 molecules after 600 h. © 2013 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2013, 51, 3404–3411 Abstract : CO2 capturing and releasing behavior of a linear polyamidine having a hexamethylene linker has been investigated in solution as well as in the solid state. The polyamidine captures and releases CO2 in an aqueous solution to the same level as a common polyamine, polyethyleneimine. In contrast, a binary system consisting of the polyamidine and polyethylene glycol absorbs CO2 much more efficiently than that with the polyethyleneimine and polyethylene glycol.